New improved incision-tubing approach for bronchoesophageal Fistula with mediastinal abscess after esophagectomy: A case report - Cao, Jianwei; Geng, Mingfei; Huang, Xiaoyu; Liu, Changjiang; Li, Hui (Frontiers in Surgery, 2023)
Bronchoesophageal fistula is a serious threat to the survival after esophagectomy for esophageal cancer. The erosion of mediastinal abscess post anastomotic leakage is the most likely directly cause. However, the bronchoesophageal fistula with gastric conduit necrosis and mediastinal abscess is refractory to either surgical or conservative treatment. In the article, a unique case of Bronchoesophageal fistula with mediastinal abscess after gastric conduit necrosis is presented. A 74-year-old female was detected the right inferior bronchus-esophageal fistula with mediastinal abscess on 15 postoperative day after esophagectomy for esophageal cancer. A successful new improved minimally invasive management was performed.